Guest Editorial: Evaluation and the Local Foods Data Void - Corry Bregendahl; Craig Chase (Journal of Agriculture, Food Systems, and Community Development, 2016)
First paragraphs: Local and regional food system professionals are obliged to rely on imperfect, incomplete, and evolving measures to track economic changes in the local food industry. These data are critical for informing decisions on how to invest limited resources to create optimal impacts. U.S. Department of Agriculture (USDA) Census of Agriculture figures indicate that direct food sales in the U.S. appeared to have increased from US$1.2 billion in 2007 to US$1.3 billion in 2012 — but when adjusted for inflation, sales actually remained steady. These figures, however, do not account for local food sales to institutions, restaurants, and retailers. The 2008 Agricultural Resource Management Survey (ARMS) partially addressed this gap by tracking local food sales from farmers to both individuals and "intermediated" markets such as restaurants and grocery stores. But the ARMS data did not include local food sales to institutions such as schools or hospitals, thus leaving another gap in the data.